2017
DOI: 10.1002/rth2.12010
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐mapping assay for monitoring antiplatelet therapy during mechanical circulatory support in children: A retrospective observational study

Abstract: Essentials Thromboelastography (TEG)‐platelet mapping (PM) assay is used for antiplatelet‐drug monitoring.The TEG‐PM was evaluated for dypiridamole and aspirin monitoring in 4 BH‐implanted children.Some TEG‐PM tracings were atypical leading to wrong results.The TEG‐PM has to be improved for antiplatelet‐drug monitoring during ventricular assistance. IntroductionThe complex hemostatic changes associated with Berlin Heart (BH) implantation in children require a challenging antithrombotic treatment. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…14,15 Similarly, other investigators have considered greater than 50% to 70% AA inhibition in children to be associated with full inhibitory effect by this assay. [16][17][18][19] To our knowledge, standardized reference ranges for % AA inhibition via TEG-PM in children have not been identified in the literature. 5 The TEG-PM assay for the contribution of AA is used to test ASA effectiveness.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Similarly, other investigators have considered greater than 50% to 70% AA inhibition in children to be associated with full inhibitory effect by this assay. [16][17][18][19] To our knowledge, standardized reference ranges for % AA inhibition via TEG-PM in children have not been identified in the literature. 5 The TEG-PM assay for the contribution of AA is used to test ASA effectiveness.…”
Section: Methodsmentioning
confidence: 99%
“…66 67 Many publications have suggested that TPM-AA/ADP percent inhibition is unreliable. 67 68 69 70 The experience of the authors of this article is in line with the results of these studies. 71 There is a growing amount of clinical experience and scientific literature supporting the successful use of MA-AA/ADP parameters that measure residual platelet activity when stimulated with AA or ADP agonists.…”
Section: Role Of Viscoelastic Assays In Platelet Function Assessmentmentioning
confidence: 99%
“…The mechanism underlying this phenomenon has not been clarified. 66,67 Many publications have suggested that TPM-AA/ADP percent inhibition is unreliable. [67][68][69][70] The experience of the authors of this article is in line with the results of these studies.…”
Section: Role Of Viscoelastic Assays In Platelet Function Assessmentmentioning
confidence: 99%